Off the hook: mutual absolution of responsibility by fathers and the state, the experiences of separated and divorced Irish mothers. (1st October 2019) - Crosse, Rosemary; Millar, Michelle
Abstract : This paper explores the experiences of 15 Irish mothers who have undergone a legal separation and/or divorce and highlights that while both parents have a legal responsibility to care for children in the event of a dissolution of marriage, the enforcement of such responsibilities is deficient in the case of the absent parent. This is particularly deleterious for mothers living in poverty and we question the adequacy of current policy to deal with changing family circumstances. The narratives of the mothers show that their lived reality is exacerbated by the failure of the state to enforce fathers' obligations to their children at the time of separation and divorce, a situation which is untenable 21 years after the introduction of divorce.